2021
DOI: 10.1155/2021/3973924
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous versus Surgical Intervention for Severe Aortic Valve Stenosis: A Systematic Review

Abstract: Aortic stenosis is a disease that is increasing in prevalence and manifests as decreased cardiac output, which if left untreated can result in heart failure and ultimately death. It is primarily a disease of the elderly who often have multiple comorbidities. The advent of transcatheter aortic valve therapies has changed the way we treat these conditions. However, long-term results of these therapies remain uncertain. Recently, there has been an increasing number of studies examining the role of both surgical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 150 publications
(209 reference statements)
0
1
0
Order By: Relevance
“…Patients who develop AKI following valve replacement have a significantly higher length of inpatient stay and higher 30-day and one-year mortality [ 51 , 52 ]. PARTNER Trials revealed no significant difference in the risk of development of AKI following SAVR or TAVR [ 53 ]. Similar results were reported by Thongprayoon et al [ 54 ].…”
Section: Reviewmentioning
confidence: 99%
“…Patients who develop AKI following valve replacement have a significantly higher length of inpatient stay and higher 30-day and one-year mortality [ 51 , 52 ]. PARTNER Trials revealed no significant difference in the risk of development of AKI following SAVR or TAVR [ 53 ]. Similar results were reported by Thongprayoon et al [ 54 ].…”
Section: Reviewmentioning
confidence: 99%